Like : a history of the world's most hated (and misunderstood) word - Reynolds, Megan C. (New York : Harper One / Harper Collins Publishers, 2025)
"A comprehensive and thought-provoking investigation into one of the most polarizing words in the English language"--
Includes bibliographical references.
Keywords: Like (The English word); Usage of word; English Language